INCREASING MATHEMATICS LEARNING OUTCOMES THROUGH THE APPLICATION OF THE PLANE GEOMETRY EXPLORATION METHOD IN MIND CLASS CHILDREN AT SLB-IT YTPA KALISAT - sugiarto, Muhammad agus (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
one group of mentally retarded children whose level of intelligence is still mild and still has the ability to learn mathematics has the possibility of obtaining academic education up to elementary grades four or five and can learn simple skills that discuss improving mathematical results through the application of the Plane Geometry Exploration Method in mentally retarded children Mild Class V at SLB-IT YTPA Kalisat Jember, this classroom action research aims to describe the improvement in learning outcomes in mathematics through the application of the plane geometry exploration method to mild mentally retarded children of class V at SLB-IT YTPA Kalisat. The research subjects were children with mild mental retardation class V at SLB-IT YTPA Kalisat District. Jember, totaling 10 students. To facilitate data collection in this study the method used is the science subject test method. Data The data analysis technique used in this PTK is a quantitative descriptive analysis technique. The results of classroom action research in order to improve the quality of learning in mild mental retardation can be discussed. First, in general, the increasing learning outcomes of students in the above categories from cycle to cycle indicate the criteria for improving the quality of learning in this classroom action research. Second, improving the quality of learning geometric shapes, which in this case is characterized by an increase in student learning outcomes and student participation in class; began to become visible from before cycle to cycle I, and the improvement in the quality of learning from cycle I to cycle II was even more evident. Where in cycle II the acquisition of student learning outcomes all reached the criteria. Thus it can be concluded, that there was an increase in learning outcomes with the plane geometry exploration method in mathematics